Perilaku Agresi pada Mahasiswa Ditinjau dari Kematangan Emosi - Guswani, Aprius Maduwita; Kawuryan, Fajar (Jurnal Psikologi: PITUTUR, 2011)
This study aimed to examine the correlation between  emotional  maturity  with  agressive behavior in collegian. Subject in this study are technique  and  law  collegian  in  Muria  Kudus University. The participants took by accidental sampling.  Agressive  behavior  and  emotional maturity scale are used   to get the data. The data analysed  by product moment. Coeficient correlation  result  the  both  variables  is  rxy=-0,906 with p=0,000 (p<0,01). It’s  mean  there  is  significant  negative correlation  between  emotional  maturity  and agressive  behavior.  More  higher  emotional maturity, lower agressive behavior can get, the opposite,  lower  emotional  maturity  make agressive  behavior  more  higher.  Effective giveness  emotional  maturity  to  agressive behavior is 82%.